Osmotic potential of nutrient solution in snapdragon growth and quality - Cruz-Crespo, Elia; Can-Chulim, Álvaro; Mancilla-Villa, Oscar Raúl; Luna-Fletes, Jonás Alán (Revista Mexicana de Ciencias Agrícolas, 2024)
On the market, there are cultivars of snapdragon flowers that belong to a particular series and group, depending on the range of nocturnal temperature they tolerate; however, even within the same series, the cultivars may have different responses to a defined environment and management. The research aimed to compare different osmotic potentials of the nutrient solution on the growth and quality of snapdragon (Antirrhinum majus L.), cultivars Red and Rose, during the autumn-winter cycle in Nayarit. The treatments were obtained through a 5 x 2 factorial arrangement; the factors were the osmotic potential (-0.036, -0.054, -0.072, -0.09, -0.108 MPa) and the cultivar (Red and Rose). These were established in September 2018 in Xalisco, Nayarit. The design of the experiment was completely randomized with 15 replications. The variables evaluated were stem length and diameter, total fresh biomass, dry leaf and stem biomass, SPAD readings, dry root biomass, root volume, spike length, dry spike biomass, number of buds and flowers, days to flowering, and days to harvest. The osmotic potentials of -0.036 and -0.054 MPa obtained the highest values in the different growth variables; these were the most suitable for greater growth and production of cut snapdragon flowers. It was also observed that, in the growth variables, the Rose cultivar stood out and was classified in the special category; on the other hand, Red was harvested earlier and classified in the sophisticated category, under the conditions of the experiment.
Keywords: Antirrhinum majus; cultivars; nutrition